Identification of microbial communities associated with Phymatotrichopsis omnivora sclerotia in two Texas fields - Sturdivant, Maxwell; Antony-Babu, Sanjay; Pierson, Elizabeth; Chappell, Thomas M.; Isakeit, Thomas (Frontiers in Microbiomes, 2025)
The soilborne fungus Phymatotrichopsis omnivora causes a mid- to late-season disease known as cotton root rot (CRR). In the United States, P. omnivora is primarily found in Arizona, New Mexico, Oklahoma, and Texas in soils that are alkaline, calcareous, and rarely freeze deeply. This fungus has a wide host range, and can cause substantial losses in cotton crops. In Texas, not all cotton-producing soils have widespread CRR despite having the characteristics to support P. omnivora. Considering the lack of CRR in some Texas soils, we hypothesize that this absence could be due to the microbial composition associated with sclerotia of P. omnivora. The objective of this study was to identify the taxa that make up microbial communities associated with P. omnivora sclerotia in different soils during both the cotton-growing and off seasons. The microbiota associated with P. omnivora sclerotia were identified by burying lab-generated sclerotia in cotton-producing soils. These sclerotia were recovered, along with soil samples for metabarcoding targeting the 16S rRNA gene and the internal transcribed spacer region. When compared to bulk soil, microbial communities associated with sclerotia differed in community composition and taxa relative abundance between a soil with widespread CRR and one in which the disease is absent. Within these soil communities, potential bacterial and fungal biomarkers that reduce CRR were identified. Furthermore, microbial communities of P. omnivora sclerotia changed seasonally. This study presents the first detailed characterization of microorganisms associated with P. omnivora sclerotia in different cotton-producing soils. Our findings support the view that P. omnivora sclerotia serve as ecological hubs, shaping microbial communities with possible implications for disease suppression. Several enriched taxa are culturable, offering candidates for future biocontrol studies that could inform disease management strategies that focus on increased microbial competition.